Ambient air pollution and daily hospital admissions for cardiovascular diseases in Arak, Iran - Vahedian, Mostafa (ARYA Atheroscler, 2017)
BACKGROUND: Outdoor air pollution has been considered as one of the most serious health concerns over the last decade. This study aimed to investigate the association between ambient air pollution and cardiovascular hospital admissions. METHODS: This investigation was carried out from January 1, 2010 to December 31, 2015, in the urban population of Arak, Iran. Daily records of concentrations of air pollutants including particulate matter less than 10 µm (PM10), nitrogen dioxide (NO2), particulate matter less than 2.5 µm (PM2.5), ozone (O3), carbon monoxide (CO), and sulfur dioxide (SO2) as well as the daily number of hospital admissions due to cardiovascular disease were inquired from the Arak Department of Environment and two major hospitals, respectively. Time-series regression analysis was used to evaluate the effect of the pollutants on cardiovascular hospital admissions with different lag structures, controlling for weather variables, seasonality and long-term time trends, and day of the week. RESULTS: Each 10 µg/m3 increase in PM10 and NO2 and 1 mg/m3 increase in CO concentrations at lag 0 (day) were significantly associated with an increase of 0.7% (P = 0.004), 3.3% (P = 0.006), and 9.4% (P < 0.001), respectively in overall cardiovascular hospital admissions. The elderly were more susceptible than those under 60 years to exposure to the pollutants (especially NO2) with regard to cardiovascular hospital admission. CONCLUSION: The results of this study showed that hospital admission for cardiovascular disease is partly related to the levels of ambient air pollutions in Arak. Susceptibility to air pollutants varies by age groups and sex.